Analisis Perilaku Konsumen Dalam Keputusan Pembelian Produk Celebrity Endorser - Mutholiah, Furiha; Widiyanto, Widiyanto (Universitas Negeri Semarang, 2021)
The use of celebrity as an endorser influences the consumption psychology of consumer. The purpose of this research was to analyze the factors considered by the consumers, the steps of purchase decision made by the consumers and consumer behavior in making decision after purchasing of Semarang Roru Cake. The data collection techniques used were observation and interview. The validity of the data using regular observation, triangulation, peer review and detailed description. Data reduction, presentation, and conclusion were the data analysis techniques. The result showed that consumer behavior in making purchase decision on Celebrity Endorser Products (A Case Study: The consumer of Roru Cake Outlet in Semarang)”. Consisted of seven factors that influenced the consumers before buying the cake, they were Product Factor, Price Factor, Promotion Factor, Personal Factor, Social Factor, Cultural Factor and Environmental and Situation Factor. There were several stages of purchase decision made by Semarang Roru Cake consumers, they included the stages of need recognition, information searching, alternative evaluation, purchasing decision and post-purchase behavior. In purchase behavior, every consumer was different in deciding what to buy, complex buying behavior, purchasing behavior that reduced the inconvenience, purchasing behavior due to purchasing habit and behavior which seeked for the variations.